PRICE AND PRODUCT QUALITY AS STRONGER DRIVERS THAN SERVICESCAPE IN STUDENT-ORIENTED COFFEE SHOP - Sari, Maya Permata; Afifah; Septivani, Mega Dwi; Gustiawan, Willson; Phung, Manh-Trung (Universitas Islam Negeri Alauddin Makassar, 2026)
Purpose - The aim of this study is to examine the effect of price, product quality, and servicescape on customer satisfaction in the modern coffee shop, Workas Coffee and Eatery, in Padang, Indonesia Methods - A quantitative methodology was employed utilizing survey data from 100 student consumers chosen via non-probability sampling. The measurement and structural models were evaluated using Structural Equation Modeling–Partial Least Squares (SEM-PLS) in SmartPLS 4. Findings - The findings demonstrate that servicescape does not exert a significant influence on customer satisfaction (β = 0.081, p = 0.148), whereas price (β = 0.472, p < 0.001) and product quality (β = 0.344, p < 0.001) exhibit positive and significant effects. The model accounts for 60.3% of the variance in customer satisfaction (R²adj = 0.603). Research Implications - The findings indicate that student patrons in contemporary coffee shops exhibit greater sensitivity to price and product quality than to the physical ambiance, implying that management should emphasize value-for-money propositions and uniform product standards. Originality -This study integrates price, product quality, and servicescape in a single model focused on a student segment in a modern Indonesian coffee shop.